Enhancing Human Resource Capacity for Sustainable Tourism Village Management in Ciamis Regency - Hidayat, Syarif; Pribadi, Pandu; Nurohman, Arip (The Indonesian Institute of Science and Technology Research, 2025)
Tourism villages in Ciamis Regency, West Java, possess significant potential for sustainable tourism development. Nevertheless, village tourism managers encounter numerous challenges, including limited comprehension of sustainability principles, insufficient environmental management, lack of access to financial and human resources, and constraints in strategic planning. This qualitative study, conducted through observations, interviews, and document analysis, investigates these challenges and evaluates the effectiveness of a capacity-building training program tailored for tourism village managers. Grounded in community engagement theory, the program emphasized participatory learning, innovation, and collaborative governance. The findings demonstrate that the training enhanced managerial competencies in sustainable tourism development, fostered innovation in tourism product design, and improved stakeholder engagement. The integration of local wisdom, environmental conservation, and community empowerment emerged as key components in building competitive and sustainable rural tourism destinations. The study contributes to the academic discourse on sustainable rural tourism and highlights the strategic role of targeted training and community involvement in achieving long-term development goals.